2008
DOI: 10.1097/coc.0b013e31815a438f
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose Escalation Study With Irinotecan, Capecitabine, Epirubicin, and Granulocyte Colony-Stimulating Factor Support for Patients With Solid Malignancies

Abstract: The recommended doses for phase II studies: irinotecan 180 mg/m2 day 1, epirubicin 50 mg/m2 day 2, and capecitabine 750 mg/m2 twice daily days 2 to 7 of each 21-day cycle. This combination is reasonably active and warrants evaluation in the phase II setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Besides hematological disturbances several other effects, including diarrhea, hand-foot syndrome, hypotension, abdominal pain, and asthenia have been reported [19]. Therefore, in the light of the research performed so far, blood toxicity seems to be a major side effect of CAP.…”
Section: Introductionmentioning
confidence: 99%
“…Besides hematological disturbances several other effects, including diarrhea, hand-foot syndrome, hypotension, abdominal pain, and asthenia have been reported [19]. Therefore, in the light of the research performed so far, blood toxicity seems to be a major side effect of CAP.…”
Section: Introductionmentioning
confidence: 99%
“…These SSBs lead to formation of double strand breaks during DNA synthesis and subsequent apoptosis. CAMP was evaluated in phase I [23] and phase II [24] clinical trials for breast cancer but was found to be too toxic for further use. Irinotecan is approved for use in colon cancer and in phase II clinical trials has shown activity against metastatic breast cancer [25, 26].…”
Section: Introductionmentioning
confidence: 99%